2001
DOI: 10.1073/pnas.061021398
|View full text |Cite|
|
Sign up to set email alerts
|

Planetary exploration in the time of astrobiology: Protecting against biological contamination

Abstract: CorrectionsECOLOGY. For the article ''Water-borne cues induce chemical defense in a marine alga (Ascophyllum nodosum)'' by Gunilla B. Toth and Henrik Pavia, which appeared in number 26, December 19, 2000, of Proc. Natl. Acad. Sci. USA (97, 14418-14420; First Published December 5, 2000; 10.1073͞pnas.250226997), the authors note the following correction. The sentence on lines 8 and 9 in the second column on page 14419 should read ''. . . and the wet-weight change (WWC) of each agar disc was calculated by subtra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
46
0
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(48 citation statements)
references
References 18 publications
0
46
0
2
Order By: Relevance
“…A specific and timely concern is the nature of analogs that are appropriate for forthcoming missions that will engage in biological studies of in situ and returned Martian samples. For example, it is conceivable that materials used in simulations of a sample return mission would, for the purpose of verifying the curation and dispersal procedures, be subject to the same planetary protection regulations as a real sample (Rummel 2001). As part of such a process, qualification samples with no detectable organic content would be needed.…”
Section: Resultsmentioning
confidence: 99%
“…A specific and timely concern is the nature of analogs that are appropriate for forthcoming missions that will engage in biological studies of in situ and returned Martian samples. For example, it is conceivable that materials used in simulations of a sample return mission would, for the purpose of verifying the curation and dispersal procedures, be subject to the same planetary protection regulations as a real sample (Rummel 2001). As part of such a process, qualification samples with no detectable organic content would be needed.…”
Section: Resultsmentioning
confidence: 99%
“…The goal of planetary protection as stated in NASA policy is prevention of forward and backward contamination (42). This policy applies directly to the control of terrestrial organisms contaminating spacecraft intended to land, orbit, fly by, or be in the vicinity of extraterrestrial bodies.…”
Section: Discussionmentioning
confidence: 99%
“…This policy applies directly to the control of terrestrial organisms contaminating spacecraft intended to land, orbit, fly by, or be in the vicinity of extraterrestrial bodies. Viking mission landers were terminally heat sterilized to decrease the risk of forward contamination of Mars and to ensure that terrestrial microorganisms did not contaminate the life detection experiments (42). However, the cost of designing and assembling the Viking landers was increased dramatically due to this requirement.…”
Section: Discussionmentioning
confidence: 99%
“…Several investigations, both culture based and culture independent, have demonstrated that a variety of bacterial taxa are repeatedly isolated under clean room conditions (18,24,26; P. Vaishampayan, S. Osman, G. Andersen, and K. Venkateswaran, submitted for publication). However, despite a growing understanding of the diverse microbial populations present in SAC, predicting the true risk of any such microbes' compromising the findings of extraterrestrial life detection efforts remains a significant challenge (30). A better understanding of the distribution and frequency at which high-risk contaminant microbes are encountered on spacecraft surfaces would significantly aid in assessing the threat of forward contamination (33).…”
mentioning
confidence: 99%